Mortality by opioid poisoning in children and teenagers and opioid prescriptions - Elise Cranfield; Elizabeth Ashcroft; Patrice Forget (BMC, 2021)
Abstract Background No comparisons between mortality from opioids in children and teenagers and opioid prescription patterns have been made in England. Aim To investigate if an association exists between mortality rates from opioid poisoning in persons aged 19 years old and under and community opioid prescription in England. Methods A retrospective analysis was undertaken for 2016 to 2019, comparing community opioid prescriptions and mortality rates from opioid poisoning. Results The number of opioid prescriptions decreased over the study period (− 2.4%, p < 0.001). Most deaths due to opioid poisoning in children and teenagers were seen in those under one year old and those aged between 15 and 19 years old (Kruskal-Wallis: p = 0.12; Dunn's test: p = 0.01). Deaths in all age ranges did not change significantly (Poisson Regression Analysis: p > 0.05). Conclusion Despite the reduction in community opioid prescriptions, there was no decrease in the number of deaths in children and teenagers due to opioid poisoning.